UJI KUALITAS CAMPURAN ABU SEKAM PADI DAN SERBUK ABU ECENG GONDOK SEBAGAI BAHAN AGREGAT HALUS PEMBUATAN BATAKO - Asriyati, Asriyati; Iswadi, Iswadi (JFT : Jurnal Fisika dan Terapannya, 2017)
This study aimed to compare the effect of adding aggregate rice husk ash and ash hyacinth of compressive strength and water absorption in the brick material, as well as great knowing the composition of the addition of rice husk ash and ash water hyacinth on the brick material. This study uses a beam-shaped test samples with a length of 15 cm, a width of 8 cm and 6 cm high with the addition of fine aggregate composition that varies the normal, 10%, 20%, 30% and 40%. Brick-making with a mixture of sand, cement, water and a mixture of rice husk ash and ash water hyacinth. The drying process is naturally carried out for 28 days. Testing the compressive strength of concrete blocks using forney engine while testing for absorption of water soaking for 24 hours. Based on test results obtained by each parameter is for the compressive strength with samples of rice husk ash (SP) is minimum 24.87 kg / cm2 and the maximum is 98.04 cm / kg2, for ash water hyacinth (EG) as a minimum 65.41 kg / cm2 and the maximum is 111.69 kg / cm2 and the mixing of the two materials (SP + EG) as a minimum 43.53 kg / cm2 and the maximum is 66.56 kg / cm2 (according to ISO standards 03-0349-1989); the value of water absorption of rice husk ash (SP) is minimum 7.30% and maximum 19.32%, for the ash water hyacinth (EG) is minimum 1.21% and maximum 1.33% and for the mixing of the two materials (SP + EG) at a minimum of 8.05 and maximum 13.71 (according to the standard SNI03-0349-1989).Â Keywords: Brick, Compressive strength, Water absorption, Rice hulls, Water hyacin.